Sistem Monitoring dan Penyiraman Tanaman Sawi Daging Berbasis Internet Of Things (IoT) - Muhammad Rindy Saputra; Maria Ulfah; Hilmansyah (ELECTRON Jurnal Ilmiah Teknik Elektro, 2023)
Beef mustard greens are an annual plant that can only be harvested once. Beef mustard greens require air with humidity above 60% RH and soil humidity between 512-307 ADC in order to grow optimally. In the gardens where this system is implemented, the method of watering the mustard greens is still done manually by garden workers. The design of this system was created to monitor and carry out automatic watering of mustard greens plants both directly and remotely. The test results of the tool system update the data taken by the soil moisture and DHT11 sensors in real time. Apart from that, the system automatically waters the mustard greens plants if the air humidity value is below 60% RH and the soil humidity is above the value of 512 ADC. In the end, this system was created with the hope of making the work of workers in implementation plantations easier by increasing the number of smart-argiculture systems.